Patterns of Change in 18th-Century English : A Sociolinguistic Approach. - Nevalainen, Terttu; Palander-Collin, Minna; Säily, Tanja (Amsterdam/Philadelphia : John Benjamins Publishing Company, 2018)
Eighteenth-century English is often associated with normative grammar. But to what extent did prescriptivism impact ongoing processes of linguistic change? Basing their work on a variationist sociolinguistic approach, the authors introduce models and methods used to trace the progress of linguistic changes in the "long" 18th century, 1680-1800.
Chapter 15. Changes in different stages -- 15.1 Introduction -- 15.2 From incipient to mid-range and beyond -- 15.2.1 Time courses of change -- 15.2.2 Sociolinguistic patterns -- 15.2.3 Issues of change in productivity -- 15.3 From nearing completion to completed -- 15.3.1 Time courses of change -- 15.3.2 Sociolinguistic patterning of recessive variants -- 15.3.3 Changing indexicalities -- Chapter 16. A wider sociolinguistic perspective -- 16.1 Rate and phase of change -- 16.2 Social patterns -- 16.2.1 Gender -- 16.2.2 Social status -- 16.2.3 Region -- 16.2.4 Real and apparent time -- 16.3 Social evaluation and register -- 16.4 The problem of continuation -- 16.5 Historical backprojection? -- References -- Appendix: Editions in the Corpora of Early English Correspondence -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books